Nonablative facelift in Indian skin with superpulsed radiofrequency - Jaishree Sharad (Wolters Kluwer Medknow Publications, 2011)
Aims: To evaluate the effect of nonablative superpulsed radiofrequency used for skin tightening and improvement of skin folds in Indian patients. Settings and Design: One hundred patients in the age group of 35-65 years with laxity of skin over face and neck were taken up for study using superpulse radiofrequency. Methods and Materials: Superpulsed radiofrequency is a biterminal, monopolar device which delivers current at the frequency of 1.75 MHz. In this study, current was delivered to the tissue with a capacitive electrode with a diameter of 25 mm. Power of 100-120 W, frequency of 18 Hz and pulse width of 50 ms was used. Statistical Analysis Used: Chi-square test, nonparametric Friedman test. Results: Evaluation was done by two independent observers on the basis of comparative photographs taken before treatment and then monthly after treatment for up to 6 months. A quartile grading scale was used. Patient satisfaction scores matched the clinical improvements observed. Ninety four patients completed a 6 month follow up. The age groups taken were 31-40 years, 41-50 years, 51-60 years, and >60 years and various areas were studied. The difference in improvement in all areas except glabellar folds across all age groups was found to be statistically significant. Conclusions: Nonablative face lift with a superpulsed radiofrequency machine is a safe, convenient and quick office procedure with excellent cosmetic results. It is noninvasive and there is no downtime. It can be used in all skin types and is safe on Indian skin. Longterm studies of effect of nonablative radiofrequency treatment on Indian skin is required.